A implementação de um protocolo criptográfico para geração distribuída de credenciais no sistema civis - SÁ, Matheus Oliveira Leite de (2019)
The electronic election system CIVIS is based on a cryptographic protocol that enables resistance to coercive attacks. In order to resist such attacks, this protocol uses the concept of credentials. A credential consists of a set of bits that must be generated by a set of electoral authorities and delivered to each voter in secrecy. Otherwise, the protocol does not guarantee resistance to coercive attacks. In this way, the generation of credentials becomes a critical point in the protocol. In the current version of the CIVIS system, however, each credential is generated by single electoral authority. As a consequence, the system relies on this authority to be trusted to ensure secure credential generation. In this context, this work presents an implementation of a protocol for the distributed generation of credentials in order to make credential generation more secure in the CIVIS system.